2012
DOI: 10.3390/toxins4121468
|View full text |Cite
|
Sign up to set email alerts
|

A Saccharomyces cerevisiae Wine Strain Inhibits Growth and Decreases Ochratoxin A Biosynthesis by Aspergillus carbonarius and Aspergillus ochraceus

Abstract: The aim of this study was to select wine yeast strains as biocontrol agents against fungal contaminants responsible for the accumulation of ochratoxin A (OTA) in grape and wine and to dissect the mechanism of OTA detoxification by a Saccharomyces cerevisiae strain (DISAABA1182), which had previously been reported to reduce OTA in a synthetic must. All of the yeast strains tested displayed an ability to inhibit the growth of Aspergillus carbonarius both in vivo and in vitro and addition of culture filtrates fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…Biological approaches to remove mycotoxin contamination have received increased attention worldwide, as biological methods are safer, more efficient and more environmentally friendly than physical and chemical strategies for contamination control. Several microbes and enzymes have been reported to be able to degrade OTA, and some practical biological strategies have already been exploited (Böhm et al 2000;Stander et al 2000Stander et al , 2001Varga et al 2000Varga et al , 2005Abrunhosa et al 2002Abrunhosa et al , 2010Cubaiu et al 2012;Armando et al 2013;Shi et al 2014). However, the identification of new microbes with the ability to degrade mycotoxins and their mechanisms of degradation will lead to improved ways to remove mycotoxins.…”
Section: Degradation Of Ochratoxin a Bymentioning
confidence: 97%
See 1 more Smart Citation
“…Biological approaches to remove mycotoxin contamination have received increased attention worldwide, as biological methods are safer, more efficient and more environmentally friendly than physical and chemical strategies for contamination control. Several microbes and enzymes have been reported to be able to degrade OTA, and some practical biological strategies have already been exploited (Böhm et al 2000;Stander et al 2000Stander et al , 2001Varga et al 2000Varga et al , 2005Abrunhosa et al 2002Abrunhosa et al , 2010Cubaiu et al 2012;Armando et al 2013;Shi et al 2014). However, the identification of new microbes with the ability to degrade mycotoxins and their mechanisms of degradation will lead to improved ways to remove mycotoxins.…”
Section: Degradation Of Ochratoxin a Bymentioning
confidence: 97%
“…According to Cubaiu et al (2012), the HPLC instrument (Agilent 1100 Series, Santa Clara, CA, USA) contained a fluorescence detector set at 333 nm excitation and 460 nm emission wavelengths. The analysis was carried out with an Agilent Eclipse XDB-C18 column (150 × 4.6 mm I.D., 5 μm particle size; Agilent) at a column temperature of 30°C, an injection volume of 20 μl and a flow rate of 1.0 ml min −1 .…”
Section: Hplc Analysis Of Ota With Fluorescence Detectionmentioning
confidence: 99%
“…This could be proposed as a possible mode of action of this biocontrol yeast in suppressing fungal growth and this might be attributed to competition for space or for a specific growth‐limiting factor and production of substances that affect hyphae integrity (Cubaiu et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…Cubaiu et al . () reported that the highly inhibition in the fungal growth was obtained by using either the fresh extracellular crude or the autoclaved supernatant of S. cerevisiae .…”
Section: Resultsmentioning
confidence: 99%
“…), Saccharomyces cerevisiae (Cubaiu et al . ), Phaffia rhodozyma (Péteri et al . ), Pichia guilliermondii (Patharajan et al .…”
Section: Discussionmentioning
confidence: 99%